Separation of auto shredder residue materials using an air table to achieve highly efficient recycling rate. Issue 14 (22nd September 2021) - Lee, Hansol; Lee, Hoon
ABSTRACT: End-of-life vehicles (ELVs) contain valuable materials such as ferrous metal 75%. The dismantling ELVs typically requires the manual separation for removing the most hazardous materials and the mechanical recovery for recycling recyclable materials. After this process, the remaining materials are referred to as automotive shredder residue (ASR). For recycling ASR, wet treatments used in most of the plants require additional processing which increases the overall operating costs and decreases throughput. Therefore, to address these problems, a newly designed air table was applied. We then analyzed the quality and recovery rate of various materials. By using this method, we achieved ELVs recycling rate of 95%.